Environmental risk assessment of a biogas station. Issue 4 (30th November 2015) - Trávníček, Petr; Kotek, Luboš; Junga, Petr
Abstract : This article investigates the environmental risk assessment of a biogas station, in particular an example attached to a wastewater treatment plant. Such analysis focused on assessing the environmental risk presented by leakage of liquid material from the biogas reactor into a neighboring river. The risk methodology proposed herein is based on the principle of risk assessment regarding a major incident within the petrochemical industry. The threat of environmental damage from biogas production is low, when compared with the petrochemical industry, but represents a branch of industry worthy of heightened health, safety, and risk methodologies. © 2016 American Institute of Chemical Engineers Process Saf Prog 35: 360–364, 2016